Masculinities, violence and culture - Hatty, Suzanne (Sage series on violence against women., 2000)
This book explores the relationship between masculinity and violence within the context of cultural change and escalating violence. This unique analysis links the growing sociological and psychological literature on masculinity with contemporary criminological research. The author focuses on: - A critical examination of the major biological, psychological, sociological, and anthropological models of masculinity and violence - Formulating an integrated theoretical approach to the relationship between violence and masculinity - Violence as a gendered activity - Representation.